Nursing workload predictors in Catalonia (Spain): a home care cohort study Variables predictoras de las cargas de trabajo de enfermería en Cataluña: seguimiento de una cohorte de atención domiciliaria - Joan Gené Badia; Alícia Borràs Santos; Joan Carles Contel Segura; Mª Dolors Camprubí Casellas; Francisco Cegri Lombardo; Antonio Heras Tebar; Ramón Noguera Rodríguez; Susana González Martínez; Anna Oliver Olius; Martiño Piñeiro González; Teresa Montanuy Baró; Esther Limón Ramírez; et al. (Elsevier, 2011)
Objective: To identify the characteristics of chronic patients and their environment in order to predict the nursing workload required 1 year after their inclusion in a home care program. Methods: A longitudinal study was carried out in 72 primary health care teams in Catalonia (Spain) with a 1-year follow-up of 1,068 home care patients over 64 years old. The variables collected from each patient included data on health and social status (Charlson and Barthel indexes and the Pfeiffer, Braden and Gijon scales), carer overburden (Zarit scale), hospital admissions, use of emergency services, self-perceived health (SF-12) and the number of health worker visits. Results: Patients received 7.2 (SD 10.4) visits per year from their nurse-in-charge, out of a total of 8.7 (SD 13.1) nursing visits per year. Risk factors for receiving more nursing visits at home were male gender (IRR=1.42, 95%CI: 1.20-1.67), dependency for daily activities (IRR=1.65, 95%CI: 1.29-2.13), decubitus ulcers (IRR=4.03, 95%CI: 2.27-7.14) and receiving emergency medical care at home (IRR=1.65, 95%CI: 1.31-2.07). In contrast, patients with major cognitive impairment (IRR=0.78, 95%CI: 0.63-0.98) had a lower probability of receiving nursing visits at home. Conclusions: Workload can be predicted by patients' clinical characteristics. The positive correlation of workload with variables related to disease severity and the negative correlation with variables related to cognitive impairment show that home care nursing in Catalonia is basically demand-oriented. Objetivo: Identificar las características basales de los pacientes crónicos y su entorno que predicen la carga de trabajo de enfermería durante el año siguiente a su inclusión en un programa de atención domiciliaria (ATDOM). Métodos: Estudio longitudinal realizado en 72 equipos de atención primaria de salud en Cataluña. Seguimiento durante un año de 1068 pacientes de ATDOM mayores de 64 años de edad. Variables recogidas: nivel de salud y situación social (test de Charlson, Barthel, Pfeiffer, Braden y Gijón); sobrecarga del cuidador (Test de Zarit); ingresos hospitalarios y visitas a urgencias; estado subjetivo de salud (SF-12); visitas de los profesionales de salud. Resultados: Los pacientes recibieron 7,2 (DE: 10,4) visitas anuales de su enfermera habitual. Observamos que tienen más riesgo de recibir visitas de enfermería los pacientes varones (IRR=1,42, IC95%: 1,20-1,67), con dependencia para las actividades de la vida diaria (IRR=1,65, IC95%: 1,29-2,13), afectados por úlceras por decúbito (IRR=4,03, IC95%: 2,27-7,14) y que precisaron servicios de atención de urgencia a domicilio (IRR=1,65, IC95%: 1,31-2,07). Por otro lado, los pacientes con deterioro cognitivo importante tienen menos probabilidad de recibir visitas de su enfermera (IRR=0,78, IC95%: 0,63-0,98). Conclusiones: Las características clínicas de los pacientes permiten predecir la carga de trabajo de enfermería. Esta relación positiva de la carga de trabajo con las variables relacionadas con la gravedad de la enfermedad y la relación negativa con el deterioro cognitivo muestra que la enfermería domiciliaria en Cataluña está básicamente orientada a la demanda.